“Moskal's,” “Separs,” and “Vatniks”: The Many Faces of the Enemy in the Ukrainian Satirical Songs of the War in the Donbas - Shuvalova, Iryna (East/West, 2022)
This article examines representations of the enemy in the Ukrainian satirical songs pertaining to the Russo-Ukrainian war in the Donbas. I focus primarily on the output of Orest Liutyi (the stage persona of Antin Mukhars'kyi) and the semi-anonymous Mirko Sablich (Mirko Sablic) collective. Using the method of multimodal discourse analysis, I examine how the enemy opposing the Ukrainian Army is portrayed in the song lyrics and the accompanying music videos. Considering the complex nature of the conflict and the lack of uniformity in the backgrounds of the warring parties, I am particularly interested in who and why is identified as the enemy in the songs. The enemy appears in several guises: “moskal's”—Russian or pro-Russian aggressors from outside Ukraine; “separs”—Ukrainian collaborators who support, often through military efforts, the separation of the Donbas from Ukraine; and “vatniks”—passive anti-Ukrainian individuals who live in Ukraine and whose inaction is perceived to be harmful to Ukraine’s wartime efforts. Whereas these songs call upon Ukrainians to repel the external enemy (“moskal's”) in armed combat, no clear strategy is suggested for how the internal enemies (“separs” and “vatniks”) should be dealt with or, in some cases, even identified. As a result, Liutyi and Sablic, while positioning themselves as “counterpropaganda” projects, risk labelling as “the enemy,” and thus alienating, the audiences most susceptible to propaganda, who could otherwise benefit most from their myth-debunking efforts.